Aktivitas Antibakteri dan Karakteristik Edible Film dengan Penambahan Serbuk Daun Jati (Tectona grandis L.) - Ika Fathya Diva Auliya; Masrukan; Ambar Rukmini; Dyah Titin Laswati (Universitas Widya Mataram, 2025)
Edible film is a thin layer used to coat food or placed between food components, and it is consumable. This research aimed to assess the effect of adding teak leaf powder on the physical, chemical, and antibacterial properties of the edible film. The experiment was designed using a Completely Randomized Design (CRD), with teak leaf powder (J) as the independent variable. Four treatments were applied: J0 (0 g), J1 (0.25 g), J2 (0.50 g), and J3 (0.75 g) of teak leaf powder. Each formulation was tested for moisture content, thickness, tensile strength, elongation, water vapor transmission rate (WVTR), and antibacterial activity against environmental bacteria and Escherichia coli. The data obtained were analyzed using ANOVA followed by Tukey’s post hoc test at a significance level of α = 0.05. Physically, the addition of teak leaf powder increased the thickness of the edible film but decreased its tensile strength, elongation, and WVTR. The chemical parameter, moisture content, remained relatively stable across all treatments. In terms of antibacterial properties, the inhibition zone against environmental bacteria increased significantly. For Escherichia coli, no inhibition zone was observed in treatment J0, while treatments J1 to J3 demonstrated comparable antibacterial effectiveness.